Practice-Based Learning for Enhancing Teachers’ Capabilities in AR Media Production and LMS-Based Learning Management: Evidence From Remote Schools in Maluku - Arjanto, Paul; Rumtutuly, Fransheine; Makulua, Izak Jakobis; Matitaputty, Christi; Makaruku, Vando Kristi; Lorwens, Aprilya Christy; Yaki, Missy Yane Lusye (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
Remote island regions in Maluku face persistent challenges such as limited internet connectivity, fragile infrastructure, and varied ICT competencies among teachers, which hinder the sustainability of digital learning. This study aimed to design and implement an integrated learning management sequence using the Moodle LMS combined with Assemblr AR media, and to evaluate its impact on teachers’ capacities in the context of remote schools. The research employed a quasi-experimental one-group pretest–posttest design involving 10 teachers at SDN 1 Waelata. The intervention included practice-based training and mentoring in LMS use (courses, activities, assessments) and no-code AR media production, measured through two pre–post instruments. Results demonstrated consistent and significant improvements: in AR production, mean scores increased from 7.9 to 16.8; in LMS management, from 8.7 to 17.2. Wilcoxon tests were significant for both (AR: Z = −2.848, p = 0.004, r ≈ 0.90; LMS: Z = −2.879, p = 0.004, r ≈ 0.91), with no negative ranks or ties, supported by operational evidence (activated courses, teacher–student accounts, and functioning classes). The findings conclude that an LMS–AR practice model is effective in strengthening teachers’ technical-pedagogical competencies and orchestrating digital classrooms under low-bandwidth conditions. The contribution lies in offering a replicable, auditable, and resilient TPACK–SAMR practice package for island schools. Future research should involve controlled trials with comparison groups, track student learning outcomes, examine sustainability and infrastructure issues, and explore the integration of local content across subjects.